PERANAN PEMBERIAN MAKANAN TAMBAHAN PADA ANAK UMUR 6 – 23 BULAN PADA SAAT KRISIS EKONOMI - -, Sandjaja; Mulyati, Sri; Saidin, M.; -, Suhartato; Widodo, Yekti (GIZI INDONESIA, 2005)
THE IMPACT OF FOOD SUPPLEMENTATION FOR CHILDREN AGED 6-23 MONTHS DURING ECONOMIC CRISISSupplementary feeding program (PMT) for children aged 6-23 months of poor families (Gakin) is a sub-component of Social Safety Net – Health Sector (SSN-HS) following economic crisis that hit Indonesia the end of 1997. It is intended to provide additional food and prevent deteriorating impact of nutritional status of the target. The main objective of the study was to determine the impact of PMT for children on malnutrition and growth as compared with that for children not receiving PMT. The design of the study is case control. Case was children of poor family who had or ever had received PMT for three months provided by SSN-HS in the last six months. Control was children of near poor families but who had never received PMT. Matching criteria for case and control were age, sex, and residence of the family. The study was conducted in West Java, Central Java, South Kalimantan covering 1014 cases and 1014 controls and their families. Data on child collected were current weight and height, and retrospective weight in the last 10 months. Other data collected were characteristics of chlidren and therir families including socioeconomic status, clinical examination, dietary intake including food suplement. Program implementation of PMT varied among study areas on selection criteria for child beneficiaries in addition to poor families, duration of PMT, method of distribution, type of food. There were similar characteristics between case and control in age, sex, breastfeeding, morbidity except for socioeconomic status of the family, age of father, educational attainment of parents. Foods distributed for 6-11 month old samples included supplementary food, foodstuff, cooked (rice/flour porridge+egg). Foods for 12-23 month old samples more varied than food suplement for 6-11 months old children. Nutrient content of food distributed was 268 Kcal for energy and 9.2 grams protein, below the recommended nutrient content of PMT 360-430 Kcal and 9-15 grams protein. Dietary intake were similar in both groups consisting of energy around 46% RDA and protein 67-73% RDA (excluding breast milk). This finding shows that part of PMT became substitute rather than supplement. Cases had significantly lower nutritional status in W/A and H/A anthropometric indices than control except for W/H. Growth pattern as analyzed using retrospective data found that there was faltering growth pattern in both groups. Period between three months prior to PMT to the baseline showed that more decreasing Z-score was significantly (repeated measures of ANOVA) greater in case than in control group. Three months during PMT, there was still further decreasing mean Z-score in both groups although it was not as great as three months before. This finding showed that PMT was able to prevent deteriorating nutritional status among child beneficiaries of poor families but was not able to improve their nutritional status.Keywords: food suplementation, economic crisis